Implementation of National and State Law in accordance with Pancasila - Mu’azzizah, Febriyanti Ervi (Universitas Negeri Semarang, 2018)
In a society, to guarantee togetherness in the life of the state, it is necessary to formulate a common goal or ideals which is called the state philosophy or staasidee (ide state) which functions as grondslag philosophy and common platform among fellow citizens in the context of constitutional life. The formulation of the state's philosophical basis or state ideology contained in the Preamble of the 1945 Constitution is Pancasila. The formulation of the Pancasila can also be referred to as the basic formula of the legal ideals (rechtsidee) of the Republic of Indonesia. As the ideals of the state, of course it must be formulated based on the ideals that live in the society that existed before this country was founded. Legal development is all human activities with regard to the existence and enactment of law in society. Legal development includes theoretical and practical aspects. It should be included principles in accordance with the values of Pancasila as the implementation of a pluralistic and national ideology civilization, to be a guideline for national and state law.